2014
DOI: 10.1002/2014wr015639
|View full text |Cite
|
Sign up to set email alerts
|

Physical context for theoretical approaches to sediment transport magnitude‐frequency analysis in alluvial channels

Abstract: Theoretical approaches to magnitude-frequency analysis (MFA) of sediment transport in channels couple continuous flow probability density functions (PDFs) with power law flow-sediment transport relations (rating curves) to produce closed-form equations relating MFA metrics such as the effective discharge, Q eff , and fraction of sediment transported by discharges greater than Q eff , f1, to statistical moments of the flow PDF and rating curve parameters. These approaches have proven useful in understanding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Subsequent to the publication of the study by Wolman and Miller [7], a whole array of studies approached the magnitude-frequency analysis (MFA) of flow discharge, which is an essential part of determining the effective discharge [16,39,40]. Although Wolman and Miller [7] suggested that a theoretical probability density function (PDF) can be employed to illustrate the flow regime, it was only after the 1990s that the theoretical MFA approach was perfected [8,19,23,40,41,42].…”
Section: Flow Data Frequency Analysismentioning
confidence: 99%
“…Subsequent to the publication of the study by Wolman and Miller [7], a whole array of studies approached the magnitude-frequency analysis (MFA) of flow discharge, which is an essential part of determining the effective discharge [16,39,40]. Although Wolman and Miller [7] suggested that a theoretical probability density function (PDF) can be employed to illustrate the flow regime, it was only after the 1990s that the theoretical MFA approach was perfected [8,19,23,40,41,42].…”
Section: Flow Data Frequency Analysismentioning
confidence: 99%
“…This is perhaps now regarded as a more general model with an emerging body of evidence suggesting that variability in the flow regime, drainage basin size, bed material type and other factors might be responsible for the observed variation in the frequencies of geomorphologically effective flows (for a detailed review, see [57]). It is recognised that in some cases low flows can make a significant contribution to the total annual sediment load, as discussed by Soar and Thorne [17,57] and corroborated by Sholtes et al [58], and with climate and land-use change the higher magnitude events in humid, temperate environments might become more significant, geomorphologically, in the future.…”
Section: Stream Energy Approaches In Fluvial Studies: Underpinning Comentioning
confidence: 76%
“…Subsequent to the publication of the study by Wolman and Miller [7], a whole array of studies approached the magnitude-frequency analysis (MFA) of flow discharge, which is an essential part of determining the effective discharge [16,39,40]. Although Wolman and Miller [7] suggested that a theoretical probability density function (PDF) can be employed to illustrate the flow regime, it was only after the 1990s that the theoretical MFA approach was perfected [8,19,23,[40][41][42].…”
Section: Flow Data Frequency Analysismentioning
confidence: 99%
“…The assessment of effective discharge using an analytical approach was performed according to the indications provided by Nash [19]; Vogel et al [8]; Goodwin [41]; Quader and Guo [42]; Klonksy and Vogel [23]; and Sholtes et al [40]. According to this method, the sediment transport mechanics are represented by a power function:…”
Section: Sub-bankfull Flow Frequency Flood Events In Outlining Effmentioning
confidence: 99%